Social balance as an axis of development and management in transportation cooperatives in zone 3 of Ecuador - Sánchez Salazar, Marcelo Eduardo; López Aguirre, José Fernando; Tobar Ruiz, María Gabriela; Jácome Tamayo, Sandra Patricia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The Organic Law of Popular and Solidarity Economy (LOEPS), in the second general provision determines that the organizations subject to this law, will incorporate to their management reports the SOCIAL BALANCE SHEET (BS); the research aims to demonstrate the level of compliance with the principles and social objectives regulated in article 4 and 21 of the LOEPS, the research analyzed the social balance sheets of 382 organizations domiciled in the provinces of zone 3 of Ecuador, of the group "transport cooperatives". The interviews with managers and the documentary review generated results on macro dimensions of the BS.